2022
DOI: 10.1186/s12916-022-02632-6
|View full text |Cite
|
Sign up to set email alerts
|

Maternal factors during pregnancy influencing maternal, fetal, and childhood outcomes

Abstract: Enhancing pregnancy health is known to improve the mother’s and offspring’s life-long well-being. The maternal environment, encompassing genetic factors, impacts of social determinants, the nutritional/metabolic milieu, and infections and inflammation, have immediate consequences for the in utero development of the fetus and long-term programming into childhood and adulthood. Moreover, adverse pregnancy outcomes such as preterm birth or preeclampsia, often attributed to the maternal environmental factors liste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 24 publications
1
25
0
Order By: Relevance
“…The rate of maternal events registered in our AIHA series was similar to the control group and the general population (0.07 to 37% depending on the severity and the presence of comorbidities) [5,6]. In contrast, fetal complications (22%) were more frequent than in the control group (5%) and in the general population, where preterm birth is the most common (8-10%) [7][8][9]. Particularly, stillbirth was observed in 4% of cases (11%, considering pregnancies with hemolytic events), similar to a recent meta-analysis [3], while no fetal deaths occurred in the control group.…”
Section: Resultssupporting
confidence: 65%
“…The rate of maternal events registered in our AIHA series was similar to the control group and the general population (0.07 to 37% depending on the severity and the presence of comorbidities) [5,6]. In contrast, fetal complications (22%) were more frequent than in the control group (5%) and in the general population, where preterm birth is the most common (8-10%) [7][8][9]. Particularly, stillbirth was observed in 4% of cases (11%, considering pregnancies with hemolytic events), similar to a recent meta-analysis [3], while no fetal deaths occurred in the control group.…”
Section: Resultssupporting
confidence: 65%
“…In terms of practical implications, our screening questionnaire might be an assistive tool for future digital intervention trials. Furthermore, it addresses the current call for translating research findings into clinical practice in the understudied group of pregnant women [ 60 ]. As resource and time saving tool it could be used to scale recommendations for appropriate GWG into routine gynaecological care.…”
Section: Discussionmentioning
confidence: 99%
“…These variation outcomes significantly impact pregnant women's and neonates' physiological and psychological wellbeing. 4,5 Also, those adverse pregnancy effects can cause long-term physical and neurological disorders in surviving babies, even death. 6 Previous studies have demonstrated that maternal age, multiparity, passive smoke, length of gestation, and gestational diabetes mellitus, are all associated with adverse birth outcomes.…”
Section: Introductionmentioning
confidence: 99%